Air Carrier Liability: An Overview of Legal and Practical Aspect in Nepal (Tribhuvan University Law Journal, 2025)
Warsaw Convention, 1929 and the Montreal Convention, 1999 are the two milestones achieved to make the Air regime reliable. Warsaw’s convention ensured limited liability and facilitated the infant aviation industry, while the Montreal Convention addressed genetic flaws resulting in inconsistent decisions by national courts also equitable compensation based on the principle of restitution. Nepal became a member of the Warsaw Convention on 13th May 1996, it ruled the Nepali Air space for almost 22 years. After the US-Bangla case, the government of Nepal showed commitment toward higher liability and ratified the Montreal Convention on December 15, 2018. The paper analyses both international conventions and ambiguity in the implementation of air carriers’ liability in the domestic sphere in Nepal.